Shock index: a simple clinical parameter for quick mortality risk assessment in acute myocardial infarction - Mocová, Danuše; Moťovská, Zuzana; Widimský, Petr; Dvořák, Jaroslav; Lisa, Libor; Buděšínský, Tomáš (Canadian journal of cardiology, 2011)
BACKGROUND: Primary percutaneous coronary intervention (PCI) has become the preferred reperfusion strategy in patients with ST-segment elevation myocardial infarction and cardiogenic shock. Early identification of patients at risk for developing cardiogenic shock allows rapid decision making to determine reperfusion and transportation to a PCI centre. The aim of this analysis was to evaluate shock index (SI) as a marker for patients at risk of cardiogenic shock. METHODS: A total of 644 consecutive patients (73% male) with acute myocardial infarction with ST elevations were analyzed retrospectively. Primary PCI was performed in 92% of patients, and 7% of patients underwent rescue PCI. The SI parameter was defined as the ratio of heart rate to systolic blood pressure at hospital admission. RESULTS: SI (odds ratio [OR], 81.26; 95% confidence interval [CI], 9.76-676.51; P<0.001), age (OR, 1.17; 95% CI, 1.08-1.26; P<0.001), and diabetes (OR, 4.94; 95% CI, 1.44-16.97; P<0.011) were independent predictors of mortality. In the group of patients with SI≥0.8, 20% died, whereas in the group with SI<0.8, 4% of patients died (P<0.01). CONCLUSIONS: The proposed clinical parameter SI correlates with patients' prognosis and could therefore be used as a simple indicator of mortality risk of acute myocardial infarction. The simplicity of this proposed index makes its use accessible in large-scale clinical practices for risk stratification during first contact with patients.
Keywords: Odds Ratio; odds ratio; hodnocení rizik; Female; balónková koronární angioplastika; ženské pohlaví; mortalita v nemocnicích; lidé; Survival Analysis; následné studie; míra přežití; Risk Assessment; koronární angiografie; Electrocardiography; interval spolehlivosti; elektrokardiografie; prognóza; Confidence Intervals; Humans; Risk Factors; retrospektivní studie; Follow-Up Studies; Male; Aged; Czech Republic; Shock, Cardiogenic; Angioplasty, Balloon, Coronary; rizikové faktory; Myocardial Infarction; Prognosis; analýza přežití; Survival Rate; Česká republika; Hospital Mortality; lidé středního věku; kardiogenní šok; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; infarkt myokardu; Coronary Angiography